2000
DOI: 10.1046/j.1365-2915.2000.00228.x
|View full text |Cite
|
Sign up to set email alerts
|

Anopheles arabiensis and An. funestus are equally important vectors of malaria in Matola coastal suburb of Maputo, southern Mozambique

Abstract: Transmission characteristics of malaria were studied in Matola, a coastal suburb of Maputo, the capital City, in southern Mozambique, from November 1994 to April 1996. The local climate alternates between cool dry season (May-October) and hot rainy season (November-April) with mean annual rainfall 650-850 mm. Saltmarsh and freshwater pools provide mosquito breeding sites in Matola. Malaria prevalence reached approximately 60% among people living nearest to the main breeding sites of the vectors. Plasmodium fal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
82
1
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(96 citation statements)
references
References 26 publications
8
82
1
5
Order By: Relevance
“…Peak biting after midnight has been observed in Senegal, 9,10 Chad, 8 and Kenya. 24 However, in Mozambique 13 and Tanzania, 14 high activity levels were seen as early as 9:00 pm, and in Ethiopia peak biting was seen from 7:00 pm until 9:00 pm. 42 In Macha, An.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Peak biting after midnight has been observed in Senegal, 9,10 Chad, 8 and Kenya. 24 However, in Mozambique 13 and Tanzania, 14 high activity levels were seen as early as 9:00 pm, and in Ethiopia peak biting was seen from 7:00 pm until 9:00 pm. 42 In Macha, An.…”
Section: Discussionmentioning
confidence: 98%
“…arabiensis is more variable its foraging behavior. Although the vector can be found feeding and resting indoors in some localities, [6][7][8][9][10][11] in other areas it is mainly exophagic [12][13][14][15] and exophilic. 12,16,17 Additionally, An.…”
Section: Introductionmentioning
confidence: 99%
“…funestus population. 3,[64][65][66][67][68][69][70][71] The longevity of An. funestus is particularly important because a higher proportion of malarial parasites can successfully develop and, combined with frequent exposure to infections still present in the local human population, can continue transmission into the wet season.…”
Section: Discussionmentioning
confidence: 99%
“…18 Previous reports showed that Anopheles funestus and Anopheles arabienses are the most common vectors in areas surrounding Maputo City. 19 Both species have proven to have considerable endophagic behavior, which favors the benefits of IRS and ITNs as protective measures.…”
Section: Discussionmentioning
confidence: 99%